2003
DOI: 10.1007/s00441-003-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of P2X 4 receptors studied with an ectodomain antibody

Abstract: A monoclonal antibody was developed to the extracellular domain of the rat P2X4 receptor. The antibody was highly selective among all rat P2X receptor subunits, and recognised only the oligomeric, non-denatured form of the P2X4 receptor. Immunohistochemistry showed an extensive pattern of distribution throughout the central and peripheral nervous systems, the epithelia of ducted glands and airways, smooth muscle of bladder, gastrointestinal tract, uterus, and arteries, uterine endometrium and fat cells. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…Likewise, our immunohistochemical findings revealed expressions within endothelial cells in some organs, within alveolar macrophages and bronchial epithelial cells in the lung, within the epithelial cells of proximal tubules, and within hepatocytes, neurons, and Purkinje cells, but only a very weak expression within cardiomyocytes. These results are consistent with the Western blotting and immunohistochemical results obtained in normal rats by Bo et al 24 In addition, we observed P2X1R and P2Y2R mRNA in several organs, including the brain and liver, in normal rats (using semiquantitative RT-PCR), and we demonstrated that in the normal condition, P2X1R was abundant in the lung, whereas P2Y2R was abundant in the liver. In contrast, Rice et al 25 reported P2Y2R mRNA expression in heart, kidney, lung, spleen and testis, but no expression in rat brain or liver.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, our immunohistochemical findings revealed expressions within endothelial cells in some organs, within alveolar macrophages and bronchial epithelial cells in the lung, within the epithelial cells of proximal tubules, and within hepatocytes, neurons, and Purkinje cells, but only a very weak expression within cardiomyocytes. These results are consistent with the Western blotting and immunohistochemical results obtained in normal rats by Bo et al 24 In addition, we observed P2X1R and P2Y2R mRNA in several organs, including the brain and liver, in normal rats (using semiquantitative RT-PCR), and we demonstrated that in the normal condition, P2X1R was abundant in the lung, whereas P2Y2R was abundant in the liver. In contrast, Rice et al 25 reported P2Y2R mRNA expression in heart, kidney, lung, spleen and testis, but no expression in rat brain or liver.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, in the context of chlamydial infection, it is worthwhile noting the tissue distribution of P2X 4 : vaginal epithelia had the greatest abundance of P2X 4 among rat tissues (8), and P2X 4 was the most abundantly expressed purinergic receptor in a cancer cell line of human cervical epithelial cells (63).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that P2X 4 is the most widely distributed P2X subunit in the central nervous system (Norenberg and Illes, 2000;Bo et al, 2003). However, native P2X receptor phenotypes in the brain do not resemble heterologously expressed homo/heteromeric P2X 4 channels (North, 2002).…”
Section: Discussionmentioning
confidence: 99%